Design portfolios : presentation and marketing for interior designers - Bender, Diane M. (Fairchild Books, an imprint of Bloomsbury Publishing Inc, 2017)
"Today's students of architecture, interior design, and landscape design need to master the art of marketing themselves via multiple print and digital formats. This third edition of Design Portfolios reflects contemporary portfolio practices and enables students to create portfolios that serve as both evolving collections of creative solutions to design problems and evidence of their abilities to visually relay messages. Readers will learn how to create not just a collection of design work but a unique marketing tool for a successful design career"--Resumé vydavatele
Keywords: architektura; interiéry; design; prezentace informací; art marketing; portfoliová analýza; architecture; interiors; presentation of information; portfolio analysis; příručky; handbooks and manuals